The effect of organizational capabilities towards R&D project innovation performance E&E manufacturing firm - Chee, Wei Keung (2020)
Past literature indicates an unclear relationship between organizational capabilities and project innovation performance. This study investigated the impact of organizational capabilities on Research and Development (R&D) project innovation performance of manufacturing firms to fill the gap in the literature. In this study, the researcher proposed a framework where technological, marketing, customer relationship management, and management capabilities were hypothesized to enhance R&D project innovation performance. Four research hypotheses, underpinned by researchbased view (RBV), were formulated to conduct the study. The study was a crosssectional study which employed an online survey, and was conducted in Electronic and Electrical (E&E) manufacturing firms in Penang, Malaysia. Data from 56 responses were used to test the hypotheses by using regression analysis. The result indicated that marketing and management capabilities had a significant positive impact on R&D project innovation performance. However, unexpectedly, customer relationship management and technological capabilities did not show a significant effect on R&D project innovation performance. Of the significant predictors of innovation performance, management capabilities were found to be the strongest contributor, and it follows by marketing capabilities. The present study allows researchers and practitioners to gain an in-depth knowledge about the effect of management and marketing capabilities on the R&D project innovation performance in manufacturing firms. Practitioners are suggested to enhance their organization marketing and management capabilities to boost their R&D innovation project performance. As the study considered E&E manufacturing firms in Penang only, the generalizability of the findings could be limited. Future studies may consider expanding the research to the whole of Malaysia.